2022
DOI: 10.2196/36206
|View full text |Cite
|
Sign up to set email alerts
|

eHealth Literacy and its Associated Factors Among Health Professionals During the COVID-19 Pandemic in Resource-Limited Settings: Cross-sectional Study

Abstract: Background The COVID-19 pandemic has wreaked havoc on health care systems and governments worldwide. Although eHealth literacy is acknowledged as a critical component of public health, it was overlooked during the pandemic. To assist patients and their families, health professionals should be knowledgeable about online health information resources and capable of evaluating relevant online information. In a resource-constrained situation, the level of eHealth literacy among health professionals is n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Two publications did not define the concept of eHealth literacy [ 29 , 35 ], four publications more or less described eHealth literacy without using an established definition [ 25 , 27 , 32 , 37 ], and eight used the established definition of eHealth literacy defined by Norman and Skinner in 2006 [ 7 , 8 ]. Nine of the included publications used the eHealth literacy scale (eHEALS) as a measure of eHealth literacy, which represents domains dependent on the basic individual eHealth literacy [ 25 , 26 , 30 34 , 36 , 37 ]. One publication used the Digital Health Literacy Instrument (DHLI), which represents the domains dependent on the basic individual eHealth literacy and on how the individual interacts with the eHealth system [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two publications did not define the concept of eHealth literacy [ 29 , 35 ], four publications more or less described eHealth literacy without using an established definition [ 25 , 27 , 32 , 37 ], and eight used the established definition of eHealth literacy defined by Norman and Skinner in 2006 [ 7 , 8 ]. Nine of the included publications used the eHealth literacy scale (eHEALS) as a measure of eHealth literacy, which represents domains dependent on the basic individual eHealth literacy [ 25 , 26 , 30 34 , 36 , 37 ]. One publication used the Digital Health Literacy Instrument (DHLI), which represents the domains dependent on the basic individual eHealth literacy and on how the individual interacts with the eHealth system [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, there was a statistically significant difference between the mean eHEALS score for physicians (mean score of 30.7) and nurses (mean score of 27.6) [ 37 ]. The studies from Ethiopia, which included three or more health care providers in their sample, reported a mean eHEALS score of 27.8 [ 33 ] and 29.2 [ 34 ]. The latter studies categorised eHealth literacy as high or low, and reported that 59% [ 34 ] and 70% [ 33 ] of the health care providers had high eHealth literacy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(1) currently working in South Korea as a doctor, nurse, medical technician, pharmacist, hospital employee, pharmaceutical company or medical equipment company employee, health care-related department professor, or health care-related field researcher and (2) those who voluntarily agreed to participate. The number of participants was calculated as 384, which satisfies the confidence level of 95% and the maximum sampling error of 5%, and finally, 400 people were surveyed in consideration of the dropout rate [16][17][18].…”
Section: Participantsmentioning
confidence: 99%